Finding Dory - Stanton, Andrew; MacLane, Angus; Collins, Lindsey; Strouse, Victoria; DeGeneres, Ellen; Brooks, Albert, 1947-; O'Neill, Ed, 1946-; Olson, Kaitlin; Rolence, Hayden, 2004-; Burrell, Ty, 1967-; Keaton, Diane; Levy, Eugene, 1946-; et al. (Burbank, CA : Disney, 2016)
When Dory, the forgetful blue tang, suddenly remembers she has a family who may be looking for her, she, Marlin, and Nemo take off on a life-changing quest to find them--with help from Hank, a cantankerous octopus; Bailey, a beluga whale who's convinced his biological sonar skills are on the fritz; and Destiny, a nearsighted whale shark!
Bonus extras: Piper short film; Commentary.
Originally released as a motion picture in 2016.
Voices of: Ellen DeGeneres, Albert Brooks, Ed O'Neill, Kaitlin Olson, Hayden Rolence, Ty Burrell, Diane Keaton, Eugene Levy, Idris Elba, Dominic West, Bob Peterson, Kate McKinnon, Bill Hader, Sigourney Weaver, Sloane Murray, John Ratzenberger.
MPAA rating: PG; for mild thematic elements.
DVD, NTSC region 1, widescreen (1.78:1) presentation; Dolby Digital 5.1, Dolby Digital 2.0.
Audio in English or Spanish (U.S. only); Spanish (U.S. only) subtitles; English subtitles for the deaf and hard-of-hearing (SDH); English descriptive audio track for the visually impaired.
Keywords: Anemonefishes -- Juvenile drama; Missing children -- Juvenile drama; Parent and child -- Juvenile drama; Fishes -- Juvenile drama; Memory -- Juvenile drama; Quests (Expeditions) -- Juvenile drama; Animated films; Children's films; Fiction films; Feature films; Video recordings for the hearing impaired; Video recordings for people with visual disabilities